2013
DOI: 10.2147/ijn.s40519
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced dermal delivery of diflucortolone valerate using lecithin/chitosan nanoparticles: in-vitro and in-vivo evaluations

Abstract: Abstract:The objective of this study was to prepare a suitable formulation for dermal delivery of diflucortolone valerate (DFV) that would maintain the localization in skin layers without any penetration and to optimize efficiency of DFV. Drug-loaded lecithin/chitosan nanoparticles with high entrapment efficiency (86.8%), were successfully prepared by ionic interaction technique. Sustained release of DFV was achieved without any initial burst release. Nanoparticles were also incorporated into chitosan gel at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…The values were found closely related to commercial cream even it contains 10 times less API. The ex-vivo permeation results of current study and in our previous study with nanoparticle in gel formulations showed a better accumulation in stratum corneum + epidermis layer, which is fitted to the results of those produced by Chroma Meter measurements (Ozcan et al, 2013b). A good correlation was also reported between the steroidal drug concentration in skin and the degree of skin blanching (Ishii et al, 2012).…”
Section: Pharmacodynamic Efficacy Of Formulationssupporting
confidence: 87%
See 3 more Smart Citations
“…The values were found closely related to commercial cream even it contains 10 times less API. The ex-vivo permeation results of current study and in our previous study with nanoparticle in gel formulations showed a better accumulation in stratum corneum + epidermis layer, which is fitted to the results of those produced by Chroma Meter measurements (Ozcan et al, 2013b). A good correlation was also reported between the steroidal drug concentration in skin and the degree of skin blanching (Ishii et al, 2012).…”
Section: Pharmacodynamic Efficacy Of Formulationssupporting
confidence: 87%
“…In our previous work, similar in-vitro results were obtained with lecithin/chitosan nanoparticles in gel formulations (Ozcan et al, 2013b). Pharmacodynamic and treatment efficacies of formulations were investigated with male albino Wistar rats as in-vivo studies.…”
Section: In-vivo Studiessupporting
confidence: 57%
See 2 more Smart Citations
“…Several recent studies have investigated the efficiency of this novel nanocarrier in delivering various model drugs via different routes, including oral and transmucosal administration. [18][19][20][21] However, it is believed that only hydrophobic molecules such as progesterone and natamycin can be entrapped into this self-assembled nanocarrier with high entrapment efficiency, whereas poor drug loading (DL) was observed for hydrophilic drugs. 22 Insulin is a large, highly hydrophilic protein that cannot be loaded directly into chitosan-lecithin nanocarriers.…”
Section: Introductionmentioning
confidence: 99%